A bilateral control scheme for vehicle steer-by-wire system with road feel and steering controller design. (February 2019) - Zheng, Hongyu; Hu, Jinghuan; Liu, Yahui
Steer-by-wire (SBW) system replaces the mechanical linkages in a conventional steering system with electronic actuators. However, such a steering system has problems regarding how to harmonize angle and torque close loop control strategy whilst guaranteeing SBW system stability. Towards this problem, a bilateral control scheme is proposed for SBW system with steering and road feel feedback control. A new torque and angle feedback deviation type bilateral control scheme is designed based on the analysis of several typical bilateral control schemes. In this bilateral control scheme, it only needs to measure steering wheel angle, steering wheel torque, pinion angle and steering motor torque, whilst it does not need to estimate tire and road force, neither to deploy complicated and expensive sensors or devices. The Llewellyn stability criterion and wave variable control are used to analyze the influencing factors of the stability of the SBW system and to control the stability respectively. The transparency of the SBW system is analyzed based on the impedance theory. In order to improve vehicle handling, the road feel feedback torque is designed by using a compensation controller. The bilateral control scheme and compensation controllers are implemented and their performance is experimentally validated using test vehicle. Test results demonstrate the efficiency and effect of the proposed algorithm.